Study on the Hydro-Thermal-Mechanical Characteristics of the Lime-Soil Compaction Pile in the Forming Process - Fengchuan Zhang; Jianhua Dong; Xiaoyu Yang; Bo Lian; Xuelang Wang (Advances in Materials Science and Engineering)
To study the effect of the lime-soil compaction pile on the collapsible loess foundation and the influence of water-heat-force characteristics on the soil during compaction, the field test of lime-soil compaction pile treatment of collapsible loess foundation is carried out. This paper monitors the process of soil temperature, water, and soil pressure change in the process of pile forming. According to the macroprocess and micromechanism of lime-soil compaction pile treatment of collapsible loess foundation, the qualitative law of water-heat-force change in the process of pile forming is obtained. Meanwhile, the influence of soil damage is introduced in the process of compaction expansion. The model of pore expansion under linear damage conditions in the plastic zone is established. The formula of radial stress distribution under damage conditions is given. The influence of different damage factors on the expansion process is analyzed.